Characterization of Diverse Pepper (Capsicum spp.) Germplasms Based on Agro-Morphological Traits and Phytochemical Contents - Suyun Moon; Nayoung Ro; Junhong Kim; Ho-Cheol Ko; SuKyeung Lee; Hyeonseok Oh; Bichsaem Kim; Ho-Sun Lee; Gi-An Lee (Agronomy, 2023)
Pepper (Capsicum spp.) is one of the most important crops worldwide. The fruits of Capsicum species are known to contain high amounts of vitamins and carotenoids, and they have health-promoting properties. In this study, a total of 513 pepper accessions belonging to two Capsicum species, C. annuum and C. frutescens, were investigated for their morphological characteristics and contents of phytochemicals including carotenoids, β-carotene, vitamin C, capsaicinoids, and total soluble solids. The results revealed wide variations in morphological traits and phytochemical contents between the accessions and across species. In addition, the association of fruit color and orientation with phytochemical contents was evaluated; the results indicated that germplasm with yellow-colored and pendant-oriented fruits could be important due to their high vitamin C levels. Multivariate analysis of the agro-morphological and phytochemical parameters revealed that Capsicum germplasm were clearly distinguished according to species. Furthermore, cluster analysis showed that germplasms belonged to three groups, and six genotypes were determined as being good genetic resources with high health-promoting phytochemical contents. Especially, vitamin C content was positively correlated with fruit diameter, weight, and wall thickness. Our findings revealed morphological and phytochemical characteristics potentially useful for breeding programs.